PENGARUH VAKSINASI BRUCELLOSIS PADA SAPI PERAH DENGAN BERBAGAI PARITAS TERHADAP EFISIENSI REPRODUKSI - Utami Kurniawati; Pratiwi Trisunuwati; Sri Wahyuningsih (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2010)
Brucella vaccination was not only able to reduce the prevalence of brucellosis, but it could also affect reproductive efficiency. The objective of the study was to know the effect of brucellosis vaccination on reproductive efficiency of dairy cattle in terms of service per conception (S/C), days open (DO) and calving interval (CI). Data from individual records of 100 dairy cows at parity one, two and three owned by ranchers were analyzed descriptively based on a randomized block design. The results showed that vaccination had a significant effect on days open (DO) and services per conception (S/C). (JIIPB 2010 Vol 20 No 1: 38-47).   Keywords: Brucellosis, reproductive efficiency, Vaccination